218k views
3 votes
(3,-2) 4x 4x x=3 7) -4x + y =6 Find x: -5x - y = 21 y = 4x+y=6 -5x-(4x+6) = 21 4x-6=21 +6 +6

1 Answer

4 votes

Let:


\begin{gathered} -4x+y=6_{\text{ }}(1) \\ -5x-y=21_{\text{ }}(2) \\ \end{gathered}

From (1), solve for y:


y=6+4x_{\text{ }}(3)

Replace (3) into (2):


\begin{gathered} -5x-(6+4x)=21 \\ -5x-6-4x=21 \\ -9x-6=21 \\ \text{solve for x:} \\ -9x=21+6 \\ -9x=27 \\ x=(-27)/(9) \\ x=-3 \end{gathered}

Replace the value of x into (3):


\begin{gathered} y=6+4(-3) \\ y=6-12 \\ y=-6 \end{gathered}

User Mooncrater
by
5.1k points